[OP.2A.02] UROMODULIN MODULATES THE EFFECT OF SALT ON BLOOD PRESSURE IN THE GENERAL POPULATION. (September 2016) - Ponte, B.; Pruijm, M.; Guessous, I.; Ackermann, D.; Ehret, G.; Mohaupt, M.; Paccaud, F.; Vogt, B.; Martin, P.Y.; Pechere-Berstschi, A.; Burnier, M.; Devuyst, O.; et al.
Abstract : Objective: Genome wide association studies have shown that the gene encoding for uromodulin (UMOD) is associated with hypertension. Recently, animal studies have demonstrated that UMOD modulates NaCl reabsorption driven by NKCC2. We hypothesised that the NaCl effect on blood pressure may be modulated by UMOD levels in the general population. Design and method: Urinary UMOD levels were measured in 994 participants of the SKIPOGH population-based study who completed 24 h blood pressure monitoring and 24 h urinary collection. We used mixed linear regression models to determine the association between 24 h sodium excretion and 24 h systolic (SBP) or diastolic (DBP) blood pressure. Family association was taken into account. Sodium excretion was square root transformed. Age, gender, smoking, treated hypertension, center, BMI, eGFR and 24 h urine variables (volume, creatinine, potassium) were entered as covariates in the models. As there was an interaction between sodium and UMOD excretion for SBP (p interaction = 0.002) and DBP (p interaction = 0.0012), we divided UMOD levels into low or high according to the median and stratified the analyses by UMOD groups. Results: Participants mean age was 47.5 ± 17.5 years; 51.8% were women. The mean 24 h SBP and DBP were 119.9 ± 13.9 and 78.2 ± 8.7 mmHg. Median 24 h sodium excretion was 136.0mmol (IQR 100.4–177.5) and median UMOD 40.1 mg/24 h (IQR 28.0–56.2). In multivariate analysis, sodium excretion was not associated with SBP in the lower UMOD group [n = 495; coefficient −0.21 (95% CI −0.74 to 0.32), p = 0.44] but was strongly associated in the higher one [n = 499; coefficient 0.87 (95% CI 0.36 to 1.38), p = 0.001]. Regarding DBP, we observed no significant association in the higher UMOD group [coef 0.21 (95% CI −0.10 to 0.51), p = 0.19] although there was an inverse one in the lower group [coef −0.39 (95% CI −0.73 to −0.04), p = 0.027]. Figure 1 shows the adjusted association between the sodium excretion and SBP (A) or DBP (B) according to UMOD levels. Figure. No caption available. Conclusions: These data show that the association of NaCl with blood pressure is modified by urinary UMOD levels. This is consistent with animal studies demonstrating that UMOD modulates NKCC2 activity and sodium reabsorption by the renal tubule, influencing salt sensitivity.